2021
DOI: 10.1038/s41467-021-21195-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of germ-free mosquitoes via transient colonisation allows stage-specific investigation of host–microbiota interactions

Abstract: The mosquito microbiota impacts the physiology of its host and is essential for normal larval development, thereby influencing transmission of vector-borne pathogens. Germ-free mosquitoes generated with current methods show larval stunting and developmental deficits. Therefore, functional studies of the mosquito microbiota have so far mostly been limited to antibiotic treatments of emerging adults. In this study, we introduce a method to produce germ-free Aedes aegypti mosquitoes. It is based on reversible col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 51 publications
5
81
1
1
Order By: Relevance
“…In addition to the expected differences between life stages, we found that most of the transcriptional changes were related to metabolic processes. This is consistent with other studies suggesting that bacteria play a nutritional role during larval development in mosquitoes [28,32] and fruit flies [33,34]. This is also in line with the results from a transcriptional comparison of axenic and gnotobiotic Ae.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition to the expected differences between life stages, we found that most of the transcriptional changes were related to metabolic processes. This is consistent with other studies suggesting that bacteria play a nutritional role during larval development in mosquitoes [28,32] and fruit flies [33,34]. This is also in line with the results from a transcriptional comparison of axenic and gnotobiotic Ae.…”
Section: Discussionsupporting
confidence: 93%
“…It has been proposed that bacteria in the larval gut provide the essential micronutrient riboflavin (vitamin B2), whose lack results in gut hypoxia and developmental arrest [29][30][31]. Other studies suggested that the role of bacteria during larval development is primarily nutritional [28], possibly by contributing to folate biosynthesis and/or by enhancing energy storage [32]. This is consistent with work in Drosophila showing that larval gut bacteria cooperate to establish an integrated nutritional network supporting host growth [33,34].…”
Section: Introductionsupporting
confidence: 69%
“…aegypti larvae through a process of “transient colonization.” Briefly, axenic larvae are colonized by a genetically modified strain of E. coli that can be removed during larval development, referred to as decolonization. The decolonized larvae go on to produce axenic adult mosquitoes ( Romoli et al, 2021 ).…”
Section: Reemergence Of Axenic Mosquito Modelsmentioning
confidence: 99%
“…Yet, several lines of evidence suggest that the hypoxic model may be incorrect. First, there was no difference in oxygen concentration between colonized larvae and decolonized axenic larvae ( Romoli et al, 2021 ). Here, we show that axenic Ae.…”
Section: Reemergence Of Axenic Mosquito Modelsmentioning
confidence: 99%
See 1 more Smart Citation